IMPROVED REPRODUCTIVE PERFORMANCE OF CROSSBRED CATTLE IN PURI DISTRICT OF ODISHA FOLLOWING SUPPLEMENTATION OF AREA SPECIFIC MINERAL MIXTURE - AGRAWALLA, J; SETHY, K; BEHERA, K; SWAIN, RK; MISHRA, SK; SAHOO, N; MOHAPATRA, MR; KHADENGA, S (The Indian Journal of Animal Reproduction, 2017)
Recently parturated thirty crossbred cattle were selected for the study from Kakatpur block of Puri district of Odisha. A group of cattle (n=15) were supplemented with specially formulated area specific mineral mixture @ 50 g/animal/day for 90 days, whereas, the remaining (n=15) were kept as unsupplemented controls. An increase (p
Keywords: ASMM; Cattle; Mineral; Crossbred; Reproduction